MULTIPLIKASI EKSPLAN MAHKOTA NANAS (Ananas comosus L. Merr.) VARIETAS SUSKA KUALU RIAU PADA PERLAKUAN BAP DAN NAA - Ratih Nur Khasanah; Fathurrahman (UIR Press, 2023)
The purpose of this study was to determine the interaction effect of BAP and NAA on Crown Nanas Suska Kuala. This research was carried out at the Biotechnology Laboratory of Faculty of Agriculture, Islamic University of Riau, Pekanbaru City. This research was conducted for 6 months starting from March to August 2022. The research used a Completely Randomized Factorial Design, consisting of 2 factors. The first factor was the concentration of BAP consisting of 4 levels, namely without treatment, 0.1 ppm, 1 ppm and 10 ppm. The second factor was the NAA concentration consisting of 4 levels, namely without treatment, 0.1 ppm, 1 ppm, and 10 ppm. Each treatment consisted of 3 repetitions to obtain 48 experimental units. In the experimental unit, there were 4 plants and 2 were used as observation samples taken randomly to obtain 192 plants. If the calculated F counted was greater than F table and then will be proceed with the Duncan's test (DMRT) at the p>0.05. The results showed that the interaction of BAP and NAA application to pineapple crown explants had a significantly effect on percentage of explant growth, number of leaves with BAP 10 ppm, and NAA 10 ppm, and number of roots with BAP 1 ppm and NAA 10 ppm. The main effect of BAP 10 ppm was significant on age of shoot emergence, age of root emergence, and number of roots. The main effect of NAA 10 ppm was significant on age of shoot emergence, root emergence age, and number of roots.